Native Canadian and Intelligence Testing - Darou, Wes G. (Canadian Journal of Counselling and Psychotherapy, 1992)
Research and experience has demonstrated that there are serious problems with using intelligence testing with Native clients. The norms do not hold with Natives, the tests do not have the predictive validity that is so important in the non-Native context, and there are questions about the appropriateness of the approach in general with regards to Native peoples' goals for their education systems. Several anecdotes are drawn from a vocational counsellor training program with a group of Cree and Ojibwa students, including two Native elders. The anecdotes demonstrate the validity problems and certain problems with the administration of such tests in general. It is recommended that such tests be used with local norms or not at all.